A new approach for deciphering between single and multiple accumulation events using intra-tooth isotopic variations: Application to the Middle Pleistocene bone bed of Schöningen 13 II-4. Issue 89 (December 2015) - Julien, Marie-Anne; Rivals, Florent; Serangeli, Jordi; Bocherens, Hervé; Conard, Nicholas J.
Abstract: It is often difficult to differentiate between archaeological bonebeds formed by one event such as a mass kill of a single herd, and those formed by multiple events that occurred over a longer period of time. The application of high temporal resolution studies such as intra-tooth isotopic profiles on archaeological mammal cohorts offers new possibilities for exploring this issue, allowing investigators to decipher between single and multiple accumulation events. We examined 18 O and 13 C isotopic variations from the enamel carbonate of 23 horse third molars from the Middle Pleistocene archaeological site of Schöningen. We employed a new approach to investigate processes of fossil accumulation that uses both bulk and intra-tooth isotopic variations and takes into account animal behavior, age at death and dental development to test the degree of isotopic affinity of animals from the same fossil assemblage. Oxygen and carbon isotope bulk values indicate that the horses from Schöningen 13 II-4 experienced relatively similar climatic and dietary regimes. Inter-individual differences of the bulk values of the horses sampled in the current study present nevertheless inter-individual variability similar to individuals from multi-layered localities. In addition, the intra-tooth isotopic variation of specimens of the same age at death seems to indicate that the studied cohort corresponds to a mix of individuals that recorded both similar and different isotopic histories. Finally, the conditions recorded in the isotopic signal shortly before death ( i.e., for teeth not fully mineralized) varied between sampled individuals, suggesting possible differences in the seasonality of death. Considering those results, we discuss the possibility that the horses from Schöningen 13 II-4 correspond to an accumulation of different death events.